Numerical Analysis of Geogrid Reinforced Embankment on Soft Clay - Abdul Halim, Muhammad Faris; Yahya, Nur Faezah; Tuan Ismail, Tuan Noor Hasanah; Abd Latif, Muhamad Faiz (Progress in Engineering Application and Technology, 2021)
Road embankments and other construction on natural soft clay faced a challenge in geotechnical engineering. Geogrid-reinforced is often used in conjunction with unbound base layers to enhance flexible pavement performance. Using the idea of combination bamboo as a green technology and geogrid, a technology named Bamboo as reinforced method has been proposed. Full-scale test embankments involving Bamboo and unreinforced (UR) embankments have been constructed on soft clay site at Universiti Tun Hussein Onn Campus Pagoh area. This paper presents an axisymmetric finite element (FE) model to analyze the performance of Bamboo embankment and to compare with the settlement prediction using finite element method (FEM). In FEM, the 2D PLAXIS Version 8 software was used in simulating real time of the construction of the embankment starting from distribution of filling work until end of surveillance monitoring data period. Previous findings from similar works often shows the different results obtainded between predicted and observe field data. Thus, FEM will be used as back analysis on the determination of parameters that influence the results. The comparison between the observed and predictions results shows that the Bamboo system performed as predicted decreases the settlement of soft clay.